Prognostic Significance of Left Ventricular Global Work Efficiency in Obese Patients with Acute ST-Segment Elevation Myocardial Infarction—A Pilot Study - Alexandra-Cătălina Frișan; Marius Simonescu; Mihai-Andrei Lazăr; Simina Crișan; Aniko Mornoș; Raluca Șoșdean; Andreea-Roxana Morar; Daniel-Miron Brie; Constantin-Tudor Luca; Cristian Mornoș (Diagnostics)
Background/Objectives: Obesity is increasingly common among patients with acute ST-segment elevation myocardial infarction (STEMI), potentially influencing both clinical evaluation and outcomes. Traditional echocardiographic metrics may be suboptimal for prognosis estimation in this population. Left ventricular myocardial work (LVMW) represents an emerging, load-adjusted marker of myocardial performance. This study aimed to assess the prognostic relevance of LVMW in obese STEMI patients. Methods: A total of 143 patients presenting with STEMI were prospectively enrolled and categorized based on their obesity status (body mass index ≥30 kg/m2). LVMW parameters were measured using echocardiography within 72 ± 24 h of hospital admission. The patients were monitored for major adverse cardiovascular events (MACE), defined as cardiovascular death, malignant ventricular arrhythmias, or unplanned hospitalizations due to heart failure or acute coronary syndrome. Results: During a median follow-up of 13 months (interquartile range: 6–28 months), MACE occurred in 30 patients (21%). Among obese individuals, left ventricular global work efficiency (LVGWE) emerged as the most robust predictor of adverse events, with an area under the receiver operating characteristic curve of 0.736 (95% confidence interval [CI]: 0.559–0.914; p = 0.009). A threshold value of 79% for LVGWE was identified as optimal for predicting MACE. Kaplan–Meier analysis revealed significantly lower event rates in obese patients with LVGWE ≥79% (log-rank p = 0.006). In univariate Cox regression analysis, LVGWE <79% was associated with a markedly elevated risk of MACE in obese patients (hazard ratio [HR] = 5.59; 95% CI: 1.33–23.50; p = 0.019), and remained a significant predictor in the overall cohort (HR = 2.73; 95% CI: 1.26–5.90; p = 0.010). Conclusions: LVGWE demonstrates strong prognostic utility in STEMI, particularly among obese patients. The incorporation of myocardial work indices into routine evaluation may enhance risk stratification and guide management in this high-risk subgroup.